Textlinguistic perspective in newspaper editorial texts: al-Quds al-'Arabi newspaper as a case study - Mogaji, Tijani Akinola; Jumingan, Muhammad Fauzi; Ismail, Muhd Zulkifli; Othman, Mohd Sukki; Yaqub, Muhammad Olatunde (Universiti Malaysia Sarawak, 2016)
Newspaper editorial texts are argumentative genre which occupies a prime position in the contemporary society such that policy makers are made accountable for their decisions which affect teeming mass of the people. It has been regarded as the voice of the voiceless or the silent majority of the society. This type of texts has been neglected in linguistic research for a long while, in spite of its vital roles in shaping the society. The present paper attempts an evaluation of this genre via the lenses of text linguistics which is primarily interested in the communicative bent of all forms of writings. This study adopted a qualitative descriptive analytical methodology to study the editorial genre in newspapers and a purposeful random technique was used in selecting about one hundred and fifty articles of al-Quds al-‘Arabi newspaper between September 2012 and April 2013, which center on issues of everlasting peace and stability of the middle-east region. The adopted data for the study resides in the electronic version of the newspaper. Al-Quds al-‘Arabi is a fiercely independent,political daily Arabic newspaper which is published in London since 1989 by Palestinian refugees. It is clear from the analysis that cohesion is the basic standard of text linguistics which plays significant role in the formation of the text, this is demonstrated by the presence of most elements of cohesion such as demonstrative pronouns,relative pronouns,pro-forms, references (internal & external), conjuncts,deitics, tenses and repetition in the text, whereas, there is absolutely no substitution, deletion and collocation whatsoever. In addition, other standards such as coherence, intentionality, acceptability, situationality and intertextuality also contributed to the actualization of the communicative value of this particular text.